An Exploratory Study on the Bookkeeping Practices among Pasar Tani Micro-Entrepreneurs - Halim Shuhaimi YEOP JOHARI; Cedrena NADINE; Seri Ayu Masuri MD DAUD (Communications of International Proceedings, 2020)
Micro entrepreneurs contribute significantly to economic growth, and poverty eradication through self-employment, and job creation. However, micro-entrepreneurs are believed to wrestle with effective financial recording and planning. In the absence of proper bookkeeping, business analysis, and hence future growth planning are difficult. This exploratory study draws on the Social Entrepreneurship Book Keeping Program initiated by the Faculty of Accountancy, Universiti Teknologi MARA Cawangan Selangor, in 2018. This study examines whether the micro-entrepreneurs at Pasar Tani maintain a proper record of their business transactions, and if not, what are the reasons for not doing so. Using a purposive sampling design involving sixteen micro-entrepreneurs, this study finds a striking result that half of them did not record their business transactions at all. The other half recorded their transactions but to a very limited extent. Furthermore, most of them had no accounting background and were not aware of the importance of bookkeeping for their business growth. Interestingly, 62.5% of the micro-entrepreneurs indicated that they were keen to learn more about accounting even though only 37.5% of them claimed that such a learning opportunity exists. Together, the findings of this study suggest that more accounting short courses and training programs should be organized and promoted to assist the micro-entrepreneurs with their financial recording and planning.
Keywords: Bookkeeping; Financial Records; Accounting; Micro-entrepreneurs